Effect of Incubation of Goat Manure on Growth and Yield of Sweet Corn - Saputra, Dedi; Handajaningsih, Merakati; Hermawan, Bandi (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2017)
ABSTRACTGoat manure is one of organic fertilizers used as the main input in organic farming practice in Indonesia. Since the slower availability of nutrient elements to the plants is the characteristic of this manure compared to the other manures, then research on the time of incubation needs to be evaluated. The study was conducted in Medan Baru Fields Experiment, district Muara Bangkahulu Bengkulu city. Randomized Complete Block Design was arranged for the experiment. Time incubation of goat manure in the field was single factor consisted of no incubation, 1 week before planting, 2 weeks before planting, 3 weeks before planting, and 4 weeks before planting. As much as 20 tons/ha of goat manure was incorporated in the field, no additional inorganic fertilizer was applied on sweet corn plants var. Bonanza F1. The sweetcorn plants responded better growth to treatment 4 weeks incubation of goat manure compared to treatment of no incubation. Yet incubation time of goat manure showed no significant effects on sweet corn yieldKeywords: incubation,goat manure, sweet corn, growth, yield